Application and side effects of blood flow restriction technique: A cross-sectional questionnaire survey of professionals. Issue 18 (7th May 2021) - de Queiros, Victor Sabino; Dantas, Matheus; Neto, Gabriel Rodrigues; da Silva, Luiz Felipe; Assis, Marina Gonçalves; Almeida-Neto, Paulo Francisco; Dantas, Paulo Moreira Silva; Cabral, Breno Guilherme de Araújo Tinôco
Abstract : Abstract: The physiological benefits of applying blood flow restriction (BFR) in isolation or in the presence of physical exercise have been widely documented in the scientific literature. Most investigations carried out under controlled laboratory conditions have found the technique to be safe. However, few studies have analyzed the use of the technique in clinical settings. To analyze how the BFR technique has been applied by professionals working in the clinical area and the prevalence of side effects (SEs) resulting from the use of this technique. This is a cross-sectional study. A total of 136 Brazilian professionals who perform some function related to physical rehabilitation, sports science, or physical conditioning participated in this study. Participants answered a self-administered online questionnaire consisting of 21 questions related to the professional profile and methodological aspects and SEs of the BFR technique. Professionals reported applying the BFR technique on individuals from different age groups from youth (⩽18 years; 3.5%) to older adults (60–80 years; 30.7%), but mainly on people within the age group of 20 to 29 years (74.6%). A total of 99.1% of the professionals coupled the BFR technique with resistance exercise. Their main goals were muscle hypertrophy and physical rehabilitation. The majority (60.9%) of interviewees reported using BFR in durations of less than 5 minutes and the pressure used was mainly determined through the values of brachial blood pressure and arterial occlusion. Moreover, 92% of professionals declared observing at least 1 SE resulting from the BFR technique. Most professionals observed tingling (71.2%) and delayed onset of muscle soreness (55.8%). Rhabdomyolysis, fainting, and subcutaneous hemorrhaging were reported less frequently (1.9%, 3.8%, and 4.8%, respectively). Our findings indicate that the prescription of blood flow restriction technique results in minimal serious side effects when it is done in a proper clinical environment and follows the proposed recommendations found in relevant scientific literature.